2004
DOI: 10.1080/0003942031000161045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of graded levels ofFusariumtoxin contaminated wheat in diets for fattening pigs on growth performance, nutrient digestibility, deoxynivalenol balance and clinical serum characteristics

Abstract: A dose response study was carried out with pigs in order to examine the effects of increasing dietary deoxynivalenol (DON)-concentrations on performance, clinical serum characteristics, nutrient digestibility and DON-metabolism. For this purpose, wheat contaminated naturally with Fusarium toxins was incorporated into pig diets at increasing proportions to give calculated dietary DON-concentrations of 0, 2.3 and 4.6 mg/kg during the starter period of phase 1 (14 d) of the experiment, and 0/0, 1.2/1.4, 2.3/3.7 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 10 publications
4
59
2
Order By: Relevance
“…In a pig growth study by Thanh et al (2015), pigs fed DON-contaminated diets (4.6 mg/kg) had reduced DM, energy, and fat digestibility. However, this conflicts with previous reports where feeding DON-contaminated diets had no impact (Dänicke et al, 2004b) or even increased total tract nutrient digestibility in feed-restricted pigs (Dänicke et al, 2004a). Authors attributed these fluctuations in digestibility to variations in the grain varieties used, production of cell wall-degrading enzymes by Fusarium fungi, and DON-induced changes in intestinal absorption capacity (Bracarense et al, 2012).…”
Section: Discussioncontrasting
confidence: 55%
“…In a pig growth study by Thanh et al (2015), pigs fed DON-contaminated diets (4.6 mg/kg) had reduced DM, energy, and fat digestibility. However, this conflicts with previous reports where feeding DON-contaminated diets had no impact (Dänicke et al, 2004b) or even increased total tract nutrient digestibility in feed-restricted pigs (Dänicke et al, 2004a). Authors attributed these fluctuations in digestibility to variations in the grain varieties used, production of cell wall-degrading enzymes by Fusarium fungi, and DON-induced changes in intestinal absorption capacity (Bracarense et al, 2012).…”
Section: Discussioncontrasting
confidence: 55%
“…Several studies have reported a DON-related improvement in nutrient digestibility (Goyarts and Dänicke, 2005a). In the present study, however, feeding pigs diets with barley naturally contaminated with Fusarium mycotoxins did not have a significant effect on nutrient digestibility, in agreement with Dänicke et al (2004) who reported no effect of feeding DON-contaminated diets to pigs on nutrient digestibility. The reason for this discrepancy in results is still unclear.…”
Section: Excretion Of Cell Wall Degrading Enzymes Bysupporting
confidence: 80%
“…(1 feed) has been shown to induce anorexia, decrease weight gain and impair the immune system, resulting in an increased incidence of infectious diseases and digestive disorders (Rotter et al 1994;Do¨ll et al 2003;Swamy et al 2003;Da¨nicke et al 2004cDa¨nicke et al , 2005Da¨nicke et al , 2007Pinton et al 2008). Acute higher doses induce feed refusal, increased salivation, vomiting, hemorrhagic diarrhea and circulatory shock (Pestka and Smolinski 2005;Pinton et al 2008).…”
mentioning
confidence: 99%